A case of 17-beta-hydroxysteroid dehydrogenase deficiency type 3 in adult endocrinologist practice - N. V. Molashenko; N. Yu. Kalinchenko; V. A. Ioutsi; O. S. Gurinovich; D. M. Babaeva; A. A. Voznesenskaya; N. M. Platonova; M. Yu. Yukina; A. A. Kolodkina; T. A. Ponomareva (Ожирение и метаболизм, 2023)
17β-Hydroxysteroid dehydrogenase 3 deficiency (17HSD3) is a rare autosomal recessive cause of 46, XY disorders of sex development resulting from HSD17B3 gene mutations, in which conversion of androstenedione to testosterone is impared. The clinical signs of 17HSD3 deficiency depend on the residual activity of the enzyme. The diagnosis of 17HSD3 deficiency is based on reduced testosterone/androstenedione ratio (T/AD < 0.8). Patients are usually assigned at birth and raise as female. If the diagnosis is made before puberty, gonadectomy is recommended, taking into account the risk of masculinization during the puberty and estrogen therapy initiation in this period. If the diagnosis of 17HSD3 deficiency is established during puberty, when virilization manifests, the therapeutic strategy is based on the results of comprehensive psychological testing and gender identity of a patient. In patients with more pronounced masculinization or diagnosis established shortly after birth, who are assigned at birth and raise as male, testosterone therapy is used to achieve a male phenotype. The 17HSD3 deficiency and virilization often result in a change of gender identity during puberty. The article presents a clinical case of 17-βhydroxysteroid dehydrogenase type 3 deficiency with late diagnosis due to parental will. The diagnostic approaches and management of the disease are also described.